Populasi Bakteri dan Jamur pada Daging Sapi dengan Penyimpanan Suhu Rendah - A. H. T. Prihharsanti (Universitas Sebelas Maret (UNS), 2009)
Meat is an important food but is also an ideal place for microorganism to life. Some of them might cause damage in food materials. Low storage temperature will slow down the growth of microorganisms. The purpose of the study was to know the influence of storage temperature on bacteria and mold population. Meef meat was stored at 28-30ºC(room temperature), 9-12ºC (refrigerator temperature) and 0-1ºC(freezer temperature). Length of storage time were 0;3;6;9;12;15; and 18 hours. Medium, nutrition broth was used as medium for bacterial growth and potato dextrose jelly for the mold. Variables observed were number of bacteria colonies and mold. To know the beginning of deteriotation, Eber test was done.The experimental design was Completely Ramdomized Design factorial 3x7 with 3 replications. The collected data were statistically analyzed by using variance analysis and Ducan Multiple Range Test. The storage length and the storage temperature affected (P<0,05) bacteria and mold population in the freezer. The low storage temperature in freezer resulted a smaller microorganism population in the meat. Key words: Meat, bacteria, mold, storage